CENSOS DIURNOS DE MAMÍFEROS Y ALGUNAS AVES DE GRAN TAMAÑO EN EL PARQUE NACIONAL TINIGUA, COLOMBIA - Stevenson, Pablo R.; Departamento de Ciencias Biológicas, Universidad de Los Andes, Bogotá. (2013)
Estimates on population density were made for 24 species.of mammals and 5 species ofbirds, all of relatively large body size (> 45 cm long), during 13 months at Tinigua National Park, Colombia. These estimates were made using a variation of the line transect sampling method. The primates were the most abundant group in the study area in terms of individuals per Krn2. In terms ofbiomass, Tayassu, Tapirus and Mazama were also important. Temporal variation in the estima tes was found (> 20% for all species), and this seems to be related to changes in habitat use. In spite of these variations, the density estimates found for four primate species were very el ose to those found using data oflong term studies (number of individuals per group and home range). Therefore, it is proposed that the method used could be appropriate to estímate population densities for sorne species.